The train to impossible places : a cursed delivery - Bell, P. G. (Peter Gwilym) (Square Fish, 2019)
Eleven-year-old Suzy Smith sneaks aboard the troll-operated Impossible Postal Express, which transports packages throughout the entire Union of Impossible Places. She suddenly finds herself as Deputy Post Master and is tasked with delivering a package to the evil Lady Crepuscula. But she botches her delivery by stealing a cursed snow globe containing a boy who claims there is a plot to take control of the Union.